Corn cob lightweight concrete for non-structural applications - Pinto, J. (2012)
A lightweight concrete using granulated corn cob (without corn) as an aggregate is proposed in this research work. Taking into account that corn cob, after extracting the corn, is generally considered an agricultural waste, an interesting economic and sustainable benefit may result by using it as a building material. Therefore, it can be an alternative sustainable lightweight aggregate solution in comparison to the most currently applied ones such as expanded clay, particles of cork, particles of expanded polystyrene (EPS), among others. The density, the compressive strength and the thermal insulation properties of a corn cob concrete were experimentally quantified. An expanded clay concrete was also studied as reference. The main results obtained are presented and discussed showing that the proposed corn cob concrete may have the adequate material properties required for a lightweight concrete for non-structural application purposes.